Augmented real‐time navigation with critical structure proximity alerts for endoscopic skull base surgery. (4th October 2013) - Dixon, Benjamin J.; Daly, Michael J.; Chan, Harley; Vescan, Allan; Witterick, Ian J.; Irish, Jonathan C.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Image‐guided surgery (IGS) systems are frequently utilized during cranial base surgery to aid in orientation and facilitate targeted surgery. We wished to assess the performance of our recently developed localized intraoperative virtual endoscopy (LIVE)‐IGS prototype in a preclinical setting prior to deployment in the operating room. This system combines real‐time ablative instrument tracking, critical structure proximity alerts, three‐dimensional virtual endoscopic views, and intraoperative cone‐beam computed tomographic image updates. Study Design Randomized‐controlled trial plus qualitative analysis. Methods Skull base procedures were performed on 14 cadaver specimens by seven fellowship‐trained skull base surgeons. Each subject performed two endoscopic transclival approaches; one with LIVE‐IGS and one using a conventional IGS system in random order. National Aeronautics and Space Administration Task Load Index (NASA‐TLX) scores were documented for each dissection, and a semistructured interview was recorded for qualitative assessment. Results The NASA‐TLX scores for mental demand, effort, and frustration were significantly reduced with the LIVE‐IGS system in comparison to conventional navigation (P < .05). The system interface was judged to be intuitive and most useful when there was a combination of high spatial demand, reduced or absent surface landmarks, and proximity to critical structures. The development of auditory icons for proximity alerts during the trial better informed the surgeon while limiting distraction. Conclusions The LIVE‐IGS system provided accurate, intuitive, and dynamic feedback to the operating surgeon. Further refinements to proximity alerts and visualization settings will enhance orientation while limiting distraction. The system is currently being deployed in a prospective clinical trial in skull base surgery. Laryngoscope, 124:853–859, 2014